Development of a liquid soap from the pitomba fruit peel extract (Talisia esculenta) (Research, Society and Development, 2021)
Talisia esculenta (A.ST.-HIL.) Radlk, which belongs to the Sapindaceae family and is widely consumed in natura, mainly in Northeastern Brazil. The present study aimed to develop a liquid soap with extract from the pitomba fruit rind, which is a solid residue that is usually discarded without use. The husks were crushed and stored in closed plastic bottles in a freezer until use. Subsequently, the hydroalcoholic and aqueous extracts were prepared. After this process, the extracts were analyzed for their phytochemical profile (saponins, phenols and tannins and flavonols, flavones, flavononols and xanthones). Next, liquid soap was developed. Soon after, the organoleptic parameters, pH and bulk density were analyzed. It was found that the soap showed a slight difference in the visual appearance at room temperature and refrigerator and color at room temperature, which may be associated with the presence of bioactive compounds. The pH was 5.44±0.13 and the density 1.031±0.002 g/cm3, according to the values ​​reported in the literature. The liquid soap developed had organoleptic characteristics, pH and proper bulk density. Furthermore, further research should be done for product improvements and effectiveness reviews.